The design of high performance mechatronics : high-tech functionality by multidisciplinary system integration - Schmidt, Robert Munnig; Schitter, Georg; Rankers, Adrian; Eijk, Jan van (Delft University Press, 2014)
2nd Revised Edition Since they entered our world around the middle of the 20th century, the application of mechatronics has enhanced our lives with functionality based on the integration of electronics, control systems and electric drives. This book deals with the special class of mechatronics that has enabled the exceptional levels of accuracy and speed of high-tech equipment applied in the semiconductor industry, realising the continuous shrink in detailing of micro-electronics and MEMS. As well as the more frequently presented standard subjects of dynamics, motion control, electronics and electromechanics, this book includes an overview of systems engineering, optics and precision measurement systems, in an attempt to establish a connection between these fields under one umbrella. Robert Munnig Schmidt is professor in Mechatronic System Design at Delft University of Technology with industrial experience at Philips and ASML in research and development of consumer and high-tech systems. He is also director of RMS Acoustics & Mechatronics, doing research and development on active controlled low frequency sound systems. Georg Schitter is professor at the Automation and Control Institute (ACIN) at Vienna University of Technology with a standing track record in research on the control and mechatronic design of extremely fast precision motion systems such as video rate AFM systems. Adrian Rankers is managing partner of Mechatronics Academy, developing and delivering high level courses to the industrial community, based on industrial experience at Philips in the research and development of consumer and high-tech systems. Jan van Eijk is emeritus professor in Advanced Mechatronics at Delft University of Technology. He is also director of MICE BV and partner at Mechatronics Academy, acting as industrial R&D advisor and teacher with experience at Philips in the research and development of consumer and high-tech systems.